Pre and post crisis analysis of stock price and exchange rate: evidence from Malaysia - Abdul Hamid, Baharom; Razali Chong, Royfaizal; Habibullah, Muzafar Shah (Universiti Putra Malaysia, 2008)
The furore and chaos created by the Asian financial crisis have ignited many studies on numerous subjects, and it is believed that the crisis has changed the way nations being administered and policies formed and implemented especially those regarding monetary and fiscal policies. In this study Johansen (1991) cointegration method was used and the period was divided into two sub periods, albeit pre crisis and post crisis. The results obtained are similar with a number of past literatures pointing to no long run relationship between stock price and exchange rate for both periods.